Characterizing interannual variability of glacier dynamics and dynamic discharge (1999–2015) for the ice masses of Ellesmere and Axel Heiberg Islands, Nunavut, Canada. Issue 1 (14th January 2016) - Van Wychen, Wesley; Davis, Jamie; Burgess, David O.; Copland, Luke; Gray, Laurence; Sharp, Martin; Mortimer, Colleen
Abstract: Landsat 7 and RADARSAT‐1/RADARSAT‐2 satellite images are used to produce the most comprehensive record of glacier motion in the Canadian High Arctic to date and to characterize spatial and temporal variability in ice flow over the past ~15 years. This allows us to assess whether dynamically driven glacier change can be attributed to "surging" or "pulsing, " or whether other mechanisms are involved. RADAR velocity mapping allows annual regional dynamic discharge (iceberg calving) to be calculated for 2000 and the period 2011–2015 (yielding a mean regional discharge of 2.21 ± 0.68 Gt a −1 ), and velocities derived from feature tracking of optical imagery allow for annual dynamic discharge to be calculated for select glaciers from 1999 to 2010. Since ~2011, several of the major tidewater‐terminating glaciers within the region have decelerated and their dynamic discharge has decreased. Trinity and Wykeham Glaciers (Prince of Wales Icefield) represent a notable departure from this pattern as they have generally accelerated over the study period. The resulting increase in dynamic discharge from these glaciers entirely compensates (within error limits) for the decrease in discharge from the other tidewater glaciers across the study region. These two glaciers accounted for ~62% of total regional dynamic discharge in winter 2015 (compared to ~22% in 2000), demonstrating that total ice discharge from the Canadian High Arctic can be sensitive to variations in flow of just a few tidewater glaciers. Key Points: Variability in glacier dynamics of the Canadian Arctic Variability in dynamic discharge from the Canadian Arctic Distinction between mechanisms controlling glacier dynamics within the Canadian Arctic